Augmented Reality in Superficial Temporal Artery to Middle Cerebral Artery Bypass Surgery: Technical Note. Issue 4 (24th June 2019) - Rychen, Jonathan; Goldberg, Johannes; Raabe, Andreas; Bervini, David
Abstract: BACKGROUND: Augmented reality (AR) applied to surgery refers to the virtual superimposition of computer-generated anatomical information on the surgical field. AR assistance in extracranial-intracranial (EC-IC) bypass revascularization surgery has been reported to be a helpful technical adjunct. OBJECTIVE: To describe our experience of using AR in superficial temporal artery to middle cerebral artery (STA-MCA) bypass surgery with the additional implementation of new technical processes to improve the safety and efficacy of the procedure. METHODS: Data sets from preoperative imaging were loaded and fused in a single 3-dimensional matrix using the neuronavigation system. Anatomical structures of interest (the STA, a selected M4 branch of the MCA, the middle meningeal artery [MMA], and the primary motor cortex [PMC]) were segmented. After the registration of the patient and the operating microscope, the structures of interest were projected into the eyepiece of the microscope and superimposed onto the patient's head, creating the AR surgical field. RESULTS: AR was shown to be useful in patients undergoing EC-IC bypass revascularization, mostly during the following 4 surgical steps: (1) microsurgical dissection of the donor vessel (STA); (2) tailoring the craniotomy above the recipient vessel (M4 branch of the MCA); (3) tailoring the craniotomy to spare the MMA; and (4) tailoring the craniotomy and the anastomosis to spare the PMC. CONCLUSION: AR assistance in EC-IC bypass revascularization is a versatile technical adjunct for helping surgeons to ensure the safety and efficacy of the procedure.